Bonding between information literacy and personal information management practices: a survey of electronic media journalists. Issue 5 (29th March 2022) - Haider, Usman; Batool, Syeda Hina; Malik, Amara; Mahmood, Khalid; Safdar, Muhmmad
Abstract : Purpose: Reporters are considered unique in terms of their information needs and seeking from other groups of masses. As they are running information business, the purpose of the study is to know about their skills of seeking, evaluating and engaging with information effectively and efficiently. Design/methodology/approach: A cross-sectional survey was conducted with electronic media reporters from 20 news channels to assess their information literacy skills (IL) and personal information management practices (PIM). Findings: The results indicated that the study's participants considered themselves as information literate. They perceived themselves competent and confident in IL skills for the overall scale and on its all sub-dimensions as well. Interestingly, the study findings show that IL skills affect PIM practices positively. However, they were less competent in advanced searching techniques (i.e. use of Boolean logic, truncation etc.) and cloud-based storing tools and applications. Practical implications: The study has inferences for information professionals, educators, media owners and other stakeholders. Policymakers in electronic media, particularly media libraries should offer training opportunities by organizing workshops, seminars etc. to enhance their advanced IL as well as PIM skills at workplace. Originality/value: Very few studies investigated the IL phenomenon beyond its skills and assessment aspects. The present study uniquely identified impact of IL on PIM practices of working electronic media journalists.